PROPOSED IMPROVEMENT OF RAW MATERIAL LAYOUT IN CV CMP WAREHOUSE - Pratiwi, Loren (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
CV CMP is a company operating in the plastic services industry. This company receives orders from other manufacturing companies to produce various types of products, including baby spoons, toys, broom handles, and others. To fulfill its customer orders, CV CMP has two types of warehouses: a finished goods warehouse and a raw material warehouse. Several issues have been identified in the raw material warehouse, such as incorrect use of raw materials, missing or hard-to-locate materials, and difficulties in the material retrieval process. The disorganized warehouse layout causes entry and exit pathways to be blocked by raw materials, preventing workers from using material handling equipment and hindering storage and retrieval processes. Therefore, a redesign of the raw material warehouse layout was carried out using the class-based storage method by grouping raw materials based on customers, resulting in two layout alternatives. Among these, the second alternative was selected as it has the shortest total material movement distance—929,065.63 meters—more accessible raw material placement for workers, and wider aisle spaces.